(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
New derivatives of 2,5-dihydro-2-oxofurans were synthesized by the interaction of 3-acetyl-4,5,5-trimethyl-2,5-dihydro-2-oxofuran with N-nucleophiles containing aromatic and heterocyclic substituents.